Unstable characteristics of the heat transfer pipe in the drain tank. (March 2020) - Wu, Xiangcheng; Liu, Fei; Lu, Jin; Liu, Yiwen; Zhang, Binhang; Yan, Changqi
Highlights: Nearing zero oscillation was found. The stable boiling condition prefers to stay above the line of Nsub = 1.25 × Npch . A new explanation to the generation of large bubbles was proposed. Uneven distribution of temperature was found at heat accumulation stage. Abstract: A two-layer assembly comprised of a thimble and an inserted center tube was experimentally investigated. The assembly is a natural circulation loop, whose special features include highly integration and continuous heat transfer between the center tube and the thimble. In this paper, the assembly, operated as a mini autorun heat exchanger, is used in the drain tank of molten salt reactors. The unstably operation characteristics were analyzed compared with the previous natural circulation oscillations. Three kinds of oscillations, geysering, DWO and nearing zero oscillation, were found in sequence from the cold state to saturation. A new explanation to the generation of large bubbles was proposed according to the comparison of our experimental results and other references. The analyzed results also showed that stable boiling condition prefers to stay above the line of Nsub = 1.25 × Npch . The nearing zero oscillation is a new oscillation whose feature and mechanism were discussed.